Examining the Effect of Increased Aerobic Exercise in Moderately Fit Adults on Psychological State and Cognitive Function - Basso, Julia C.; Oberlin, Douglas J.; Satyal, Medha K.; O’Brien, Catherine E.; Crosta, Christen; Psaras, Zach; Metpally, Anvitha; Suzuki, Wendy A. (Frontiers in Human Neuroscience, 2022)
Regular physical exercise decreases the risk for obesity, diabetes, and cardiovascular disease, increases life expectancy, and promotes psychological health and neurocognitive functioning. Cross-sectional studies show that cardiopulmonary fitness (VO2 max) is associated with enhanced brain health, including improved mood state and heightened cognitive performance. Interventional studies are consistent with these cross-sectional studies but most have focused on low-fit populations. Few such studies have asked if increasing levels of physical activity in moderately fit people can significantly enhance mood, motivation, and cognition. Therefore, the current study investigated the effects of increasing aerobic exercise in moderately fit individuals on psychological state and cognitive performance. We randomly assigned moderately fit healthy adults, 25 to 59 years of age, who were engaged in 1 or 2 aerobic exercise sessions per week to either maintain their exercise regimen (n=41) or increase their exercise regimen (i.e., 4 to 7 aerobic workouts per week; n=39) for a duration of 3 months. Both before and after the intervention, we assessed aerobic capacity using a modified cardiopulmonary fitness test, and hippocampal functioning via various neuropsychological assessments including a spatial navigation task and the Mnemonic Similarity Task as well as self-reported measures including the Positive and Negative Affect Scale, Beck Anxiety Inventory, State-Trait Anxiety Inventory, Perceived Stress Scale, Rumination Scale, Eating Disorders Examination, Eating Attitudes Test, Body Attitudes Test, and Behavioral Regulation of Exercise Questionnaire. Consistent with our initial working hypotheses, we found that increasing exercise significantly decreased measures of negative affect, including fear, sadness, guilt, and hostility, as well as improved body image. Further, we found that the total number of workouts was significantly associated with improved spatial navigation abilities and body image as well as reduced anxiety, general negative affect, fear, sadness, hostility, rumination, and disordered eating. In addition, increases in fitness level were significantly associated with improved episodic memory and exercise motivation as well as decreased stress and disordered eating. Our findings are some of the first to indicate that in middle aged moderately-fit adults, continuing to increase exercise levels in an already ongoing fitness regimen is associated with additional benefits for both psychological and cognitive health.